Design of a Round Tofu Printer Using the Ergo-Product Design Method : (Case Study: Mr. Andi’s Tofu Factory Palembang) - Setiawan, Heri; Susanto, Sani; Rinamurti, Micheline; Alfian, Achmad; Pratama, Yohanes Dicka; Budiarto, Dominikus (Jurnal Improsci, 2025)
Background. Tofu is the familiar Indonesian food. It is crucial to produce Tofu effectively and efficiently. Aim. This research aims to help Mr Andi's tofu factory in Palembang, which has problems with the round tofu wrapping process. Workers are often absent due to specific events, which causes the owner to experience difficulties in producing round tofu. The processing time will be slower than usual, and the owner will have to hire spare tofu wrappers with more expensive wages. This round tofu maker is designed for Mr Andi's tofu factory. Methods. The research method applies ergonomics in product design (Ergo-Product Design), which applies the AT, SHIP approach, and anthropometry. Result. The research result is a tool made based on the dimensions of round tofu, size 6.25x6.25x4 cm3. The cover, base, and pressing cloth size is 50x50x3 cm3. The core part consists of a wooden part measuring 50x50x10 cm3 and a small square inner part of aluminum measuring 6.25x6.25 cm2. The fabric presses are the same size but added with small nails made of ¾-inch mild steel positioned right in the center of each small square in the core. Conclusion. The tool manufacturing cost is 560,000 IDR, and the maintenance cost is 10,000 IDR per month. Break event point in 13,728 units or 8,227,778 IDR and payback period in 2 days. Regarding environmental aspects, liquid waste from the tofu filter still exists because it does not change the production process. Worker energy becomes lighter, down 32 kcal/hour. Implication. The tofu packaging process time is faster, and the amount of production is more significant.